Analysis and Measurement of Parameters of Quality of Life in Informal Settlements Surrounding of Tehran Metropolis. (24th June 2021) - Ghaderpour, Yousef; Arasteh Taleshmekaiil, Mohammad Reza; Rouki, Bahareh; Mohemsaz, Mona; Azimi, Mohammad Hossein; Sadeghpour, Ali
Abstract : Quality of life is a concept used to describe the development of the welfare of society, and improving the quality of life is one of the most important goals of governments around the world. Informal settlements, as one of the most vulnerable urban areas, are always in unfavorable conditions in terms of various social, economic, and physical indicators. Therefore, the main purpose of this study is to investigate the status of various quality of life indicators in informal settlements around the metropolis of Tehran in Iran. This research is descriptive, analytical, and correlational based on primary data in which the initial data are collected through the documentary and survey (field) method using a questionnaire. The collected data were processed by SPSS and SmartPLS software. Based on the results of the t -test, quality of life indices in informal settlements around the metropolis of Tehran, on a Likert scale with an average of 23.2, is at a low level. Also, the results of the PSL path modelling and multivariate regression test show that increasing the quality of social, economic, physical, service, and access indicators, in terms of residents, has the greatest impact on improving the quality of life of this urban fabric and security index. It has the least impact. There is also a significant relationship between indicators, and the mental perspective of citizens changes under social, service, economic, and physical conditions.